Interaction between the leg recovery test and subjective measures of fatigue in handball players: short-, mid-, and long-term assessment - Bauer, J.; Muehlbauer, T.; Geiger, S.; Gruber, M. (Frontiers in Sports and Active Living, 2024)
Background: The physical and mental demands of handball during training or competition often lead to fatigue which can impair performance. Many attempts have been made to assess the level of fatigue in athletes either by objective (neuromuscular performance) or subjective (questionnaires) measures, however, their interplay over short-, mid-, and long-term periods is currently unknown. Knowledge about both types of assessments is important as load management by coaches is traditionally based on direct adjustments following a training session, adjustments of content structure of training weeks between games, as well as adjustments of load management over the entire competitive season. Thus, this study aimed to investigate the interplay between objective and subjective fatigue measures at multiple test times throughout a handball season.